DAMPAK KEY AUDIT MATTERS, OPINI AUDIT, DAN FEE AUDIT PADA AUDIT DELAY - Ramadhan, Fachri Rasya; Giri, Efraim Ferdinan (Kajian Ekonomi dan Bisnis, 2025)
This research aims to analyze the effect of Key Audit Matters (KAM), Audit Opinion (OA), and Audit Fee (FA) on Audit Delay (AD) in Consumer Cyclical sector industry. The research sample consists of 100 companies selected using a purposive sampling method from a total of 166 companies during the 2022–2024 period in the Consumer Cyclical industry. The total sample used in this study is 300 company years. The data used is secondary data from annual reports on the IDX. Data analysis uses the E-Views 12 panel data regression method. The analysis was carried out on three data groups, namely: all audit delay data, audit delay < 90 days, and audit delay > 90 days. The results of this study indicate that audit opinion is an important variable that has a significant effect on audit delay, especially in the audit delay group > 90 days. The results show that KAM and FA do not have a significant effect on audit delay. The results of this study imply that audit delay still occurs and needs to be reduced to support investment decisions by investors and creditors.